A Realistic Theory of Law (Book Review) - Kabir, Syahrul Fauzul (Faculty of Law, Universitas Brawijaya, 2019)
Despite the law has been developing through the span of the history of human civilization, law has been formulated by legal thinkers, theologians, philosophers; constructed with various pretexts and objectives: for legal certainty, utility, justice and order; used to regulate social life in various forms and dimensions: customary law, religious law, state law, international law, the formulation of legal theory, to date, is still an academic debate. It is Brian Z. Tamanaha, a professor of law from America, who also entered the theoretical debate's arena through his academic works. In the contemporary legal discourse, Tamanaha is quite popular among academics and legal activists. Tamanaha is known globally due to his famous works, such as